2020
DOI: 10.3390/ijms21197014
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Tissue Plasminogen Activator (r-tPA) Induces In-Vitro Human Neutrophil Migration via Low Density Lipoprotein Receptor-Related Protein 1 (LRP-1)

Abstract: Thrombolysis is the gold standard treatment for acute ischemic stroke. Besides its fibrinolytic role, recombinant tissue plasminogen activator (r-tPA) holds several non-fibrinolytic functions. Here, we investigated the potential role of r-tPA on human primary neutrophil migration in vitro. By means of modified Boyden chamber migration assay and checkerboard analysis we showed a dose-dependent chemotactic effect of r-TPA with a maximum effect reached by 0.03 mg/mL (0.003–1 mg/mL). Pre-incubation with MAP kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The results of one study indicated LRP1 blockade could prevent intravascular adherence and neutrophil recruitment within the ischemic tissue induced by PAI-1 derived from both leukocytes and nonleukocytic sources (157). Another similar study showed that LRP1 synthesized and expressed by neutrophils accounts for the r-tPA-induced migration and degranulation of neutrophils (216), which can aggravate tissue damage and inflammation. Additionally, in a hind limb ischemia model, LRP-1 was observed to act as the receptor of cytokine midkine (MK) to support neutrophil adhesion and trafficking by promoting the highaffinity conformation of β2 integrin, suggesting a role of LRP-1 in acute inflammation (217).…”
Section: Lrp1 In Neutrophilsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of one study indicated LRP1 blockade could prevent intravascular adherence and neutrophil recruitment within the ischemic tissue induced by PAI-1 derived from both leukocytes and nonleukocytic sources (157). Another similar study showed that LRP1 synthesized and expressed by neutrophils accounts for the r-tPA-induced migration and degranulation of neutrophils (216), which can aggravate tissue damage and inflammation. Additionally, in a hind limb ischemia model, LRP-1 was observed to act as the receptor of cytokine midkine (MK) to support neutrophil adhesion and trafficking by promoting the highaffinity conformation of β2 integrin, suggesting a role of LRP-1 in acute inflammation (217).…”
Section: Lrp1 In Neutrophilsmentioning
confidence: 98%
“…In addition, neutrophils can release chemotactic proteins and proinflammatory mediators to promote monocyte recruitment as well as vascular inflammation, promoting atherosclerosis development. Furthermore, neutrophils can degranulate large amounts of different proteases including matrix metalloproteases (MMPs), myeloperoxidase (MPO) and neutrophil elastase or form neutrophil extracellular traps, leading to a thinner fibrous cap and subsquent plaque rupture (213,216). The results of one study indicated LRP1 blockade could prevent intravascular adherence and neutrophil recruitment within the ischemic tissue induced by PAI-1 derived from both leukocytes and nonleukocytic sources (157).…”
Section: Lrp1 In Neutrophilsmentioning
confidence: 99%
“…We then observed that tPA-treated neutrophils from ischemic mice exhibited an increase in the expression of the tPA receptor low-density LRP-1 ( Figure 1Q ; supplemental Figure 2C), which is consistent with findings from a recent in vitro study. 25 Furthermore, the tPA-induced PAD4 expression ( Figure 1R ; supplemental Figure 2D), H3Cit + neutrophils ( Figure 1S ; supplemental Figure 2E), and NET production ( Figure 1T ) were decreased when neutrophils were incubated with a combination of tPA and the LRP antagonist RAP.…”
Section: Resultsmentioning
confidence: 90%
“… 16,23 Peripheral blood neutrophils were seeded at a density of 5 × 10 5 cells per mL in 48-well glass-bottomed plates and treated with tPA or 10 μg/mL Klebsiella pneumoniae lipopolysaccharide (LPS; Sigma-Aldrich) for 2.5 hours at 37°C. 16 Cl-amidine (100 μM; Millipore, Burlington, MA), 24 RAP (500 nM), 25 or vehicle was added 15 minutes before addition of tPA. Cells were fixed in 2% paraformaldehyde, blocked with 3% bovine serum albumin, and incubated with rabbit anti-citrullinated histone H3 (H3Cit; 1:1000; ab5103; Abcam, Cambridge, MA), followed by incubation with Alexa Fluor 488 donkey anti-rabbit secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Since the 20th century, cardiovascular disease has become a leading cause of death in humans, and its pathogenesis is commonly related with the thromboembolic condition. Currently, thrombolytic therapy is the most effective treatment in managing thromboembolism [1][2][3]. Human tissue-type plasminogen activator (tPA) is a serine protease synthesized and secreted by vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%